Perspectives on Social Sustainability and Interior Architecture
XXIII, 141 p. 25 illus.
Keywords: This book argues that interior architects have a responsibility to practice their profession in collaborative ways that address the needs of communities and of to be the agents of social justice and cultural heritage. The book is divided into three sections, based on three pivotal themes — community engagement, social justice and cultural heritage. Each section has chapters that put forward the principles of these themes, leading into a variety of fascinating case studies that illustrate how socially sustainable design is implemented in diverse communities across the world. The second section includes four concise case studies of community housing issues, including remote-area indigenous housing and housing for the homeless. The third section offers two extensively researched essays on design and cultural heritage — a case study of the development of a redundant industrial site and a historical study of gendered domestic interiors. The book appeals to a wider audience than the design community alone and challenges mainstream interior design/interior architecture practitioners nationally and internationally to take a leading role in the field of socially responsible design. The issues raised by the authors are relevant for individuals, communities, government and non-government organisations, professionals and students. “In the twenty-first century we seem to have entered into a new world of knowledge discovery, where many of the most exciting insights come not from the authority of a traditional discipline, but from the dialogue that happens at the hubs and intersections of thought — the arenas where different disciplines and approaches, different schools and habits of thinking, come together to collaborate and contend. This collection is a good example of this, and I hope the book will be widely read and its lessons learned and applied.” Tim Costello, Officer of the Order of Australia, Chief Executive, World Vision Australia.